2015
DOI: 10.1016/j.cognition.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

In search of lost time: Reconstructing the unfolding of events from memory

Abstract: When remembering an event, not only do we recollect what happened, when and where it happened, but also how it unfolded over time. What aspects of events are encoded in memory to support this recollection? This question is central for understanding the nature of event memories and our reconstruction of the time passed. In this article, we investigate how the spontaneous encoding of unfamiliar animations during learning influences the recollection of how these animations unfold. Specifically, we examine two str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 47 publications
8
76
1
Order By: Relevance
“…Less attention to the specific animation content was evidenced in relatively poor performance in recognition memory, compared with Experiment 1, and the absence of a condition effect in recognition times-an effect replicated several times when content is attended to (Faber & Gennari, 2015a, 2015b. Because our grouping conditions were based on the number of fine-grainedperceived as the smallest-segments and their similarity, which require attention to specific details of the animations (e.g., color or shape changes), the absence of a condition effect on duration ratings is not surprising, as these specific aspects may have not been attended to, encoded, or recollected.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Less attention to the specific animation content was evidenced in relatively poor performance in recognition memory, compared with Experiment 1, and the absence of a condition effect in recognition times-an effect replicated several times when content is attended to (Faber & Gennari, 2015a, 2015b. Because our grouping conditions were based on the number of fine-grainedperceived as the smallest-segments and their similarity, which require attention to specific details of the animations (e.g., color or shape changes), the absence of a condition effect on duration ratings is not surprising, as these specific aspects may have not been attended to, encoded, or recollected.…”
Section: Discussionmentioning
confidence: 75%
“…The results of repeated measures ANOVAs with either subjects (F 1 ) or triads (F 2 ) as a random factor and recognition times as a dependent variable indicated that there was a significant main effect of condition on the response latencies, (Yonelinas, 2001), suggesting that properties of the events encoded in memory during the study phase were accessed or checked during memory judgments, with the conditions that required access to more segments and less similarity between them leading to increased response latencies. Because the implications of these recognition findings have been discussed in detail elsewhere, we do not discuss them further here (Faber & Gennari, 2015a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations in the rate of temporal signal drift may also relate to observations that event boundaries lead to exaggerated estimates of event sequence duration [50]. For instance, items appearing within the same scene context were remembered as ‘closer’ together than items spanning a scene change [27], even though the same amount of objective time had passed.…”
Section: Temporal Drift As a Mode Of Event Separationmentioning
confidence: 99%
“…In parallel, researchers in the domain of retrospective time estimation have shown that the degree of context change is a better predictor of duration judgments than alternative explanations, such as the number of items remembered from the interval (Block and Reed, 1978; Block, 1990, 1992). Indeed, changes in task processing (Block and Reed, 1978; Sahakyan and Smith, 2014), environmental context (Block, 1982), and emotions (Pollatos et al, 2014), as well as event boundaries (Poynter, 1983; Zakay et al, 1994; Faber and Gennari, 2015), lead to overestimation of past durations.…”
Section: Introductionmentioning
confidence: 99%